2006
DOI: 10.1007/s00775-005-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a [2Fe–2S] ferredoxin from Rhodobacter capsulatus likely involved in Fe–S cluster biogenesis and conformational changes observed upon reduction

Abstract: FdVI from Rhodobacter capsulatus is structurally related to a group of [2Fe-2S] ferredoxins involved in iron-sulfur cluster biosynthesis. Comparative genomics suggested that FdVI and orthologs found in alpha-Proteobacteria are involved in this process. Here, the crystal structure of FdVI has been determined for both the oxidized and the reduced protein. The [2Fe-2S] cluster lies 6 A below the protein surface in a hydrophobic pocket without access to the solvent. This particular cluster environment might explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…Cysteine residues are also found at the equivalent position to Cys 43 of Arx in Fe-S cluster biogenic ferredoxins, e.g. FDVI from Rhodobacter capsulatus (56) and Fdx from E. coli (57), and in the P450-associated ferredoxin terpredoxin (58). The corresponding residue in both Pdx and Pux is alanine while it is a leucine in Adx (24,29,59).…”
Section: Crystal Structure Of the [2fe-2s] Ferredoxinmentioning
confidence: 99%
“…Cysteine residues are also found at the equivalent position to Cys 43 of Arx in Fe-S cluster biogenic ferredoxins, e.g. FDVI from Rhodobacter capsulatus (56) and Fdx from E. coli (57), and in the P450-associated ferredoxin terpredoxin (58). The corresponding residue in both Pdx and Pux is alanine while it is a leucine in Adx (24,29,59).…”
Section: Crystal Structure Of the [2fe-2s] Ferredoxinmentioning
confidence: 99%
“…This additional cysteine residue between the first and the second cluster-binding cysteine residues was proposed to be characteristic for ISC-type ferredoxins. 17 It was suggested that this additional cysteine residue might be involved in the binding and reduction of S 0 and/or Fe 3+ . 32 However, there were also ISC-type ferredoxins reported that are lacking this special cysteine residue (e.g., Etp1 fd from S. pombe, 13 FdxB from Pseudomonas putida 33 or human Fdx2 8 ).…”
Section: Activity Of Bacterial Fdx1 In a Mitochondrial P450 Systemmentioning
confidence: 99%
“…Another interaction distinguishing vertebrate-type and plant-type ferredoxins is the hydrogen bond between the cluster-binding C44 and T46 (in Fdx1), which is also found only in the former class of ferredoxins. 17 The obligate presence of this OH-S bond explains the requirement of a threonine or a serine residue at the respective position. Apart from T46, three more residues are highly but not absolutely conserved.…”
Section: Activity Of Bacterial Fdx1 In a Mitochondrial P450 Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no crystal structure of an eukaryotic adrenodoxin-type ferredoxin involved in heme A synthesis and assembly of iron-sulfur clusters has been described, whereas three structures of bacterial proteins with corresponding function are already solved [13][14][15][16]. The corresponding E. coli ferredoxin gene was shown to be crucial for the efficient biosynthesis of Fe-S clusters in vivo [17,18], and the encoded protein was proven to support in vitro assembly of Fe-S clusters [19].…”
Section: Introductionmentioning
confidence: 99%